New graduate doctors' preparedness for practice: a multistakeholder, multicentre narrative study. Issue 8 (29th August 2018) - Monrouxe, Lynn V; Bullock, Alison; Gormley, Gerard; Kaufhold, Kathrin; Kelly, Narcie; Roberts, Camille Emilie; Mattick, Karen; Rees, Charlotte
Abstract : Objective: While previous studies have begun to explore newly graduated junior doctors' preparedness for practice, findings are largely based on simplistic survey data or perceptions of newly graduated junior doctors and their clinical supervisors alone. This study explores, in a deeper manner, multiple stakeholders' conceptualisations of what it means to be prepared for practice and their perceptions about newly graduated junior doctors' preparedness (or unpreparedness) using innovative qualitative methods. Design: A multistakeholder, multicentre qualitative study including narrative interviews and longitudinal audio diaries. Setting: Four UK settings: England, Northern Ireland, Scotland and Wales. Participants: Eight stakeholder groups comprising n=185 participants engaged in 101 narrative interviews (27 group and 84 individual). Twenty-six junior doctors in their first year postgraduation also provided audio diaries over a 3-month period. Results: We identified 2186 narratives across all participants (506 classified as 'prepared', 663 as 'unprepared', 951 as 'general'). Seven themes were identified; this paper focuses on two themes pertinent to our research questions: (1) explicit conceptualisations of preparedness for practice; and (2) newly graduated junior doctors' preparedness for the General Medical Council's (GMC) outcomes for graduates . Stakeholders' conceptualisations of preparedness for practice included short-term ( hitting the ground running ) and long-term preparedness, alongside being prepared for practical and emotional aspects. Stakeholders' perceptions of medical graduates' preparedness for practice varied across different GMC outcomes for graduates (eg, Doctor as Scholar and Scientist, as Practitioner, as Professional) and across stakeholders (eg, newly graduated doctors sometimes perceived themselves as prepared but others did not). Conclusion: Our narrative findings highlight the complexities and nuances surrounding new medical graduates' preparedness for practice. We encourage stakeholders to develop a shared understanding (and realistic expectations) of new medical graduates' preparedness. We invite medical school leaders to increase the proportion of time that medical students spend participating meaningfully in multiprofessional teams during workplace learning.